Immigrants and public open spaces : attitudes, preferences and uses - Silveirinha De Oliveira, Eva Maria; Oliveira, Eva Maria (The University of Edinburgh, 2012)
Migration is becoming a major political and social issue in a global context. However, while immigrants’ integration into the hosting society and cities has sparked research investigations, there have been few studies focusing on how their presence affects the urban fabric, especially their use of public open spaces and even less is known about how, and in what way, such spaces have an impact on the immigrants themselves. The scope of this research is to gain a better understanding of how immigrants use, perceive and experience public open spaces. The research focuses on the case study of public open spaces in Lisbon, the capital of Portugal. The thesis centres on the experience of first generation immigrants from the three largest immigrant communities living in Portugal, namely, from Brazil, Cape Verde and Ukraine. These immigrants not only represent different waves of migration but also communities from very different geographic origins and socio-cultural backgrounds. David Canter’s ‘Theory of Place’ (Canter, 1977) is used as the theoretical framework for the study, whereby place is understood to be the locus for the juxtaposition of activities that people engage in, their perceptions of it and the physical attributes of space. The key research aim is to explore immigrants’ attitudes, preferences, perceptions, uses and ‘place attachment’ in relation to public open spaces in Lisbon. A mixed-method approach is used to gather information from these three immigrant communities and to establish the relationship between them and public open spaces in the host country. The qualitative methods comprise focus-group discussions and ‘go-along’ interviews, while the quantitative methods include questionnaires. The key findings from the analysis of the cross-cultural experiences show that ‘frequency of use’ is likely to be affected by immigrants’ national and cultural identity. The analysis also reveals the particular meaning that ‘being close to water’ has for the three immigrant groups, especially in terms of its connection with the sea and going to the beach, as well as the importance to them of music being played outdoors and their need for more places to have barbecues. The findings also highlight the importance of public open spaces to immigrants’ lives, particularly in terms of how they evoke different memories (childhood and adult) and how some immigrants have already developed memories in relation to certain places and features in Lisbon. ‘Place attachment’, thus, is shown to serve as an anchor for people and it creates links between the homeland and host country, giving a sense of continuity to immigrants’ lives.
Keywords: immigrants; public spaces; Lisbon